A let-7 microRNA-binding site polymorphism in KRAS predicts improved outcome in metastatic colorectal cancer (mCRC) patients treated with salvage cetuximab/panitumumab monotherapy - Saridaki, Zenia (2014)
PURPOSE: An inherited mutation in KRAS (LCS6-variant, rs61764370) results in altered control of the KRAS oncogene. We studied this biomarker’s correlation to anti-EGFR monoclonal Antibody therapy (moAbs) response in metastatic colorectal cancer patients (mCRC) patients. EXPERIMENTAL DESIGN: LCS6-variant and KRAS/BRAF mutational status was determined in 512 mCRC patients treated with salvage anti-EGFR moAbs therapy, and findings correlated with outcome. Reporters were tested in colon cancer cell lines to evaluate the differential response of the LCS6-variant allele to therapy exposure. RESULTS: 21.2% (109/512) of mCRC patients had the LCS6-variant (TG/GG), which was found twice as frequently in the BRAF mutated versus the wt group (p = 0.03). LCS6-variant patients had significantly longer PFS with anti-EGFR moAbs monotherapy treatment in the whole cohort (16.85 vs 7.85 weeks, p = 0.019) and in the double wt (KRAS and BRAF) patient population (18 vs 10.4 weeks, p = 0.039). Combination therapy (moAbs plus chemotherapy) led to improved PFS and OS for non-variant patients, and brought their outcome to levels comparable to LCS6-variant patients receiving anti-EGFR moAbs monotherapy. Combination therapy did not lead to improved PFS or OS for LCS6-variant patients. Cell line studies confirmed a unique response of the LCS6-variant allele to both anti-EGFR moAbs monotherapy and chemotherapy. CONCLUSIONS: LCS6-variant mCRC patients have an excellent response to anti-EGFR moAbs monotherapy, without any benefit of additional chemotherapy. These findings further confirm the importance of this mutation as a biomarker of anti-EGFR moAbs response in mCRC patients, and warrant further prospective confirmation.